Level Of Physical Fitness And Body Mass Index In Students Aged 16-18 Years In Highland Areas - Ilmul Ma'arif; Puguh Satya Hasmara (Universitas Sebelas Maret, 2023)
In this study aims to determine the level of Physical Fitness and Body Mass Index The method in this study is the type of this research is a survey with quantitative descriptive methods. The research site is Madrasah Aliyah Panglungan in the highlands, the sampling technique in this study is purposive sampling technique based on age characteristics. The results of this study Based on descriptive calculations show the level of physical fitness in the moderate category of 30 students (43.48%). And student body mass index 45 (65.22%) Conclusion Based on the research objectives and data analysis of the research results regarding fitness level and BMI shows moderate and normal categories so that it can be said that students in the highlands still maintain body condition by moving activities and maintaining a diet that is consumed.